Ubiquitin and Legionella: From bench to bedside. (December 2022) - Tomaskovic, Ines; Gonzalez, Alexis; Dikic, Ivan
Abstract: Legionella pneumophila, a Gram-negative intracellular bacterium, is one of the major causes of Legionnaires' disease, a specific type of atypical pneumonia. Despite intensive research efforts that elucidated many relevant structural, molecular and medical insights into Legionella 's pathogenicity, Legionnaires' disease continues to present an ongoing public health concern. Legionella 's virulence is based on its ability to simultaneously hijack multiple molecular pathways of the host cell to ensure its fast replication and dissemination. Legionella usurps the host ubiquitin system through multiple effector proteins, using the advantage of both conventional and unconventional (phosphoribosyl-linked) ubiquitination, thus providing optimal conditions for its replication. In this review, we summarize the current understanding of L. pneumophila from medical, biochemical and molecular perspectives. We describe the clinical disease presentation, its diagnostics and treatment, as well as host-pathogen interactions, with the emphasis on the ability of Legionella to target the host ubiquitin system upon infection. Furthermore, the interdisciplinary use of innovative technologies enables better insights into the pathogenesis of Legionnaires' disease and provides new opportunities for its treatment and prevention. Highlights: Outbreaks of L. pneumophila represent an ongoing public health care problem. Host-pathogen interplay is tightly coordinated by Legionella effector proteins. L. pneumophila hijacks the host ubiquitin system using both canonical and non-canonical phosphoribosyl-linked ubiquitination. State-of-the-art techniques provide new insights into L. pneumophila pathogenesis, enabling novel translational approaches.